The dispatcher: bridging the probabilistic gap in automated decision modeling - Cherednichenko, Olga; Maliarenko, Vladyslav (Національний технічний університет "Харківський політехнічний інститут", 2025)
In the contemporary landscape of Software Engineering and Business Process Management (BPM), the integration of generative artificial intelligence has precipitated a paradigm shift from manual, deterministic specification to automated, probabilistic generation. While offering scalability, this transition introduces a fundamental volatility known as the "Probabilistic Gap"—the chasm between the fluid, high-variance output of Large Language Models (LLMs) and the strict, zero-tolerance syntactic requirements of execution engines like DMN (Decision Model and Notation). This paper addresses the "Struc-Bench Paradox," highlighting the limitations of transformer architectures in generating complex structured data without rigid orchestration. The study formally defines and implements the "Dispatcher," a pivotal control plane component designed to function as an intelligent resource arbiter and quality gatekeeper within a neuro-symbolic architecture. The theoretical framework shifts the economic focus from Baumol’s Cost Disease, which addresses production speed, to Boehm’s Law of Software Economics, which emphasizes the exponential cost of defects propagated to production. To operationalize this, the Dispatcher represents a discrete deterministic process modeled using Cost-Colored Petri Nets rather than Finite State Machines (FSMs). The Petri Net formalism allows for precise modeling of concurrency, state accumulation, and the strict enforcement of "Retry Budgets," thereby mathematically guaranteeing system termination and preventing infinite loops of costly regeneration. The architectural implementation utilizes a "Test-First" generation philosophy: the system first synthesizes validation criteria (JSON test cases) utilizing Schema Injection and RAG, and subsequently grounds the generation of DMN logic (XML) in these pre-validated scenarios. Experimental analysis was conducted using a controlled set of 200 generation cycles to evaluate two distinct error-recovery strategies: Strategy A (Independent regeneration of DMN tables only) and Strategy B (Joint/Dynamic regeneration of both DMN and Test Cases). Quantitative results demonstrate that Strategy B is economically superior, achieving a 6.06% reduction in total cost and an 8.44% reduction in token consumption compared to the independent patching approach. The findings indicate that simultaneous regeneration empowers the LLM to resolve semantic incoherence and hallucinations more effectively than iterative repairs, prioritizing logical consistency over partial code retention. The study concludes that the Dispatcher effectively bridges the neuro-symbolic divide by transforming validation from a post-production manual review into a pre-production automated cycle. By enforcing a "Stop-Loss" mechanism driven by economic constraints, the framework minimizes the Total Cost of Ownership and serves as a critical "Trust Proxy," mitigating automation bias and ensuring that AI-generated artifacts meet the rigorous reliability standards required for enterprise deployment.

У сучасному ландшафті управління бізнес-процесами (BPM) та програмної інженерії інтеграція генеративного штучного інтелекту зумовила фундаментальний зсув парадигми від ручної детермінованої специфікації до автоматизованої імовірнісної генерації. Цей перехід, забезпечуючи безпрецедентну масштабованість, створює критичний «імовірнісний розрив» між стохастичною природою великих мовних моделей (LLM) та суворими синтаксичними вимогами середовищ виконання рішень, таких як DMN (Decision Model and Notation). Дослідження фокусується на вирішенні проблеми «Struc-Bench Paradox», яка демонструє нездатність стандартних трансформерних архітектур надійно генерувати складні структуровані дані без зовнішнього керування. Центральним елементом запропонованого рішення є «Dispatcher» (Диспатчер) – архітектурний компонент, що виконує роль інтелектуального арбітра ресурсів та шлюзу якості в нейро-символічній системі. Методологічною основою роботи є перехід від економічної теорії «хвороби витрат Баумоля», яка пріоритезує швидкість виробництва, до «закону економіки ПЗ Боема», що встановлює логарифмічну залежність між часом виявлення дефекту та вартістю його виправлення. Для формалізації дискретних детермінованих процесів Диспатчера у роботі застосовано математичний апарат Мереж Петрі (Cost-Colored Petri Nets) замість класичних скінченних автоматів (FSM). Це дозволило ефективно моделювати стан системи, управляти конкурентністю процесів та суворо контролювати бюджет повторних спроб (retry budget), уникаючи ризиків нескінченних циклів регенерації та «спіралі смерті» витрат токенів. Реалізація системи базується на патерні «Test-First Generation», де процес валідації відокремлено від генерації бізнес-логіки: спочатку формуються тестові кейси (JSON), і лише на їх основі генерується DMN-модель, яка негайно перевіряється вбудованим рушієм Camunda. Емпірична частина дослідження включає аналіз ефективності двох стратегій відновлення після помилок на вибірці з 200 циклів генерації: Стратегії А (незалежна регенерація тільки таблиці DMN) та Стратегії B (спільна регенерація DMN та тестових кейсів). Результати експерименту виявили контрінтуїтивну перевагу Стратегії B, яка продемонструвала зниження загальної вартості генерації на 6,06% та скорочення споживання токенів на 8,44%, при досягненні 100% успішності валідації. Доведено, що повна регенерація контексту дозволяє LLM усунути логічні галюцинації ефективніше, ніж ітеративне виправлення окремих фрагментів коду. Отримані результати підтверджують, що Диспатчер виступає економічним щитом підприємства, забезпечуючи принцип «fail fast and fix cheap» (швидка помилка – дешеве виправлення). Впровадження запропонованого фреймворку трансформує процес створення моделей рішень з ризикованого експерименту у надійну інженерну дисципліну, де символічний валідатор виступає гарантом істини для нейронного генератора, забезпечуючи довіру користувачів та стабільність бізнес-систем
Диспатчер: подолання імовірнісного розриву в автоматизованому моделюванні рішень
Keywords: large language models; automated decision modeling; Petri nets; validation and verification; business process management; мовні моделі; автоматизоване моделювання рішень; мережі Петрі; валідація та верифікація; управління бізнес-процесами